Open Defecation in South Asia: A Literature Review of Sanitation Behaviour, Policy Approaches, and Comparative Outcomes (International Journal of Food and Nutritional Sciences, 2023)
Open defecation has long been a major public health challenge in South Asia, with India historically accounting for a disproportionately large share of the global population practicing it. Despite higher per-capita income levels and stronger state capacity than neighbouring countries, India lagged behind Bangladesh and Pakistan in reducing open defecation well into the 2010s. This literature review synthesises findings from academic studies, government reports, community-level evaluations, and international datasets to examine the determinants of sanitation behaviour, the evolution of policy interventions, and the divergent outcomes across South Asia. The review identifies four broad themes spanning the literature: structural underinvestment in sanitation and health, the importance of cultural norms and behavioural preferences, institutional weaknesses in programme implementation, and the transformative role of community mobilisation exemplified by Bangladesh’s Community-Led Total Sanitation (CLTS) movement. Evidence suggests that India’s sanitation challenge cannot be understood through economic indicators alone, as behaviour, social norms, and monitoring systems have been equally influential. Bangladesh’s experience highlights the effectiveness of behaviour-centred, community-driven strategies, in contrast to India’s emphasis on toilet construction. The review concludes that successful sanitation reform requires long-term behavioural change, strong monitoring systems, and sustained community engagement, suggesting clear lessons for Indian policy.